The effect of kick-box on violence tendency of the high school students - AYSEGUL SARIKAYA; AYSE ALPTEKIN (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This study aims to compare the violent tendencies of High School students who participate in kickboxing with those of students who do not.Method: In total, 103 licensed kickboxers from Konya were surveyed, including 18 women and 85 men. The sample was selected using a stratified sampling technique. Data analysis was performed using SPSS and LISREL. The statistical